Alternative Splicing Provides a Mechanism to Regulate LlHSFA3 Function in Response to Heat Stress in Lily. Issue 4 (14th October 2019) - Wu, Ze; Liang, Jiahui; Wang, Chengpeng; Ding, Liping; Zhao, Xin; Cao, Xing; Xu, Sujuan; Teng, Nianjun; Yi, Mingfang
Abstract : A genetic buffering mechanism of lily through alternative splicing counteracts the side effect of LlHSFA3 in response to heat stress. Abstract: Heat stress transcription factors (HSFs) are central regulators of plant responses to heat stress. Their heat-induced transcriptional regulation has been extensively studied; however, their posttranscriptional and posttranslational regulation is poorly understood. In a previous study, we established that there were at least two HSFA3 homologs, LlHSFA3A and LlHSFA3B, in lily ( Lilium spp.) and that these genes played distinct roles in thermotolerance. Here, we demonstrate that LlHSFA3B is alternatively spliced under heat stress to produce the heat-inducible splice variant LlHSFA3B-III . We further show that LlHSFA3B-III protein localizes in the cytoplasm and nucleus, has no transcriptional activity, and specifically disturbs the protein interactions of intact HSFA3 orthologs LlHSFA3A-I and LlHSFA3B-I. Heterologous expression of LlHSFA3B-III in Arabidopsis ( Arabidopsis thaliana ) and Nicotiana benthamiana increased plant tolerance of salt and prolonged heat at 40°C, yet reduced plant tolerance of acute heat shock at 45°C. Conversely, heterologous expression of LlHSFA3A-I caused opposing phenotypes, which were substantially ameliorated by coexpression of LlHSFA3B-III . LlHSFA3B-III interacted with LlHSFA3A-I to limit its transactivation function and temper the function of LlHSFA3A-I, thus reducing the adverse effects of excessive LlHSFA3A-I accumulation. Based on these observations, we propose a regulatory mechanism of HSFs involving heat-inducible alternative splicing and protein interaction, which might be used in strategies to promote thermotolerance and attenuate the heat stress response in crop plants.